What we are learning on HTLV-1 pathogenesis from animal models - Duc Dodon, Madeleine; Villaudy, Julien; Gazzolo, Louis; Haines, Robyn; Lairmore, Michael (Frontiers in Microbiology, 2012)
Isolated and identified more than 30 years ago, human T cell leukemia virus type 1 (HTLV-1) is the etiological agent of adult T cell leukemia/lymphoma, an aggressive lymphoproliferative disease of activated CD4+ T cells, and other inflammatory disorders such as HTLV-1-associated myelopathy/tropical spastic paraparesis. A variety of animal models have contributed to the fundamental knowledge of HTLV-1 transmission, pathogenesis, and to the design of novel therapies to treat HTLV-1-associated diseases. Small animal models (rabbits, rats, and mice) as well as large animal models (monkeys) have been utilized to significantly advance characterization of the viral proteins and of virus-infected cells in the early steps of infection, as well as in the development of leukemogenic and immunopathogenic processes. Over the past two decades, the creation of new immunocompromised mouse strains that are robustly reconstituted with a functional human immune system (HIS) after being transplanted with human tissues or progenitor cells has revolutionized the in vivo investigation of viral infection and pathogenesis. Recent observations obtained in HTLV-1-infected humanized HIS mice that develop lymphomas provide the opportunity to study the evolution of the proviral clonality in human T cells present in different lymphoid organs. Current progress in the improvement of those humanized models will favor the testing of drugs and the development of targeted therapies against HTLV-1-associated diseases.